Adaptive Algorithm for Chirp-Rate Estimation. (19th August 2009) - Djurović Djurović, Igor Igor; Ioana Ioana, Cornel Cornel; Stanković Stanković, Ljubiša Ljubiša; Wang Wang, Pu Pu
Abstract : Chirp-rate, as a second derivative of signal phase, is an important feature of nonstationary signals in numerous applications such as radar, sonar, and communications. In this paper, an adaptive algorithm for the chirp-rate estimation is proposed. It is based on the confidence intervals rule and the cubic-phase function. The window width is adaptively selected to achieve good tradeoff between bias and variance of the chirp-rate estimate. The proposed algorithm is verified by simulations and the results show that it outperforms the standard algorithm with fixed window width.